A Comparative Analysis of Curriculum 2013 and Merdeka Curriculum Implementation in Elementary Schools: A Case Study in Pinrang Regency - Abdul Walid; Muhardi Muhardi; Sulaiman Sulaiman; Mawardi Jalil Masri (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
The transition from Curriculum 2013 to the Merdeka Curriculum represents a strategic effort to enhance flexibility and personalization in Indonesia’s education system. This study conducts a comparative analysis of both curricula at the elementary level, focusing on philosophical foundations, curriculum structure, instructional strategies, assessment systems, and implementation challenges. A case study approach was employed through policy analysis and field observations at two elementary schools in Pinrang Regency. The findings reveal that Curriculum 2013 emphasizes standardized procedures and structured scientific approaches, which often limit instructional flexibility. In contrast, the Merdeka Curriculum adopts a phase-based structure that grants teachers greater autonomy to implement differentiated instruction responsive to students’ diverse needs. The integration of the Projek Penguatan Profil Pelajar Pancasila (P5) further strengthens contextual and character-based learning. However, the effectiveness of the Merdeka Curriculum is strongly influenced by teacher readiness and institutional capacity. This study offers empirical insights to support policymakers and schools in designing adaptive curriculum transition strategies grounded in professional development, institutional support, and contextual considerations to ensure sustainable improvement in elementary education quality.